2023
DOI: 10.3389/fnbeh.2023.1163718
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and underlying mechanisms of acupuncture therapy for PTSD: evidence from animal and clinical studies

Abstract: As a major public health problem, posttraumatic stress disorder (PTSD) has a substantial impact on individuals and society. The total excess economic burden of PTSD in the US is estimated to be more than $232.2 billion a year. Acupuncture is widely used in patients with PTSD, and an increasing number of studies have been undertaken to assess the efficacy and underlying mechanisms of acupuncture for the treatment of individuals with PTSD. However, there has not yet been a review that simultaneously elucidates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…These data extend previous work and are more definitive because of adequate power, the use of blind assessment using the CAPS-5, the combined clinical and biological effects, and the evaluation of protocol adherence. A recent systematic review by Tang and colleagues reports clinical effects of verum acupuncture for PTSD that are larger than those with psychotherapy or pharmacotherapy and mechanistic studies that demonstrate effect on systems known to be disrupted in PTSD. These authors also note that effectiveness may be strengthened by relatively high retention rates .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data extend previous work and are more definitive because of adequate power, the use of blind assessment using the CAPS-5, the combined clinical and biological effects, and the evaluation of protocol adherence. A recent systematic review by Tang and colleagues reports clinical effects of verum acupuncture for PTSD that are larger than those with psychotherapy or pharmacotherapy and mechanistic studies that demonstrate effect on systems known to be disrupted in PTSD. These authors also note that effectiveness may be strengthened by relatively high retention rates .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review by Tang and colleagues reports clinical effects of verum acupuncture for PTSD that are larger than those with psychotherapy or pharmacotherapy and mechanistic studies that demonstrate effect on systems known to be disrupted in PTSD. These authors also note that effectiveness may be strengthened by relatively high retention rates . Our study demonstrated either higher tolerability, satisfaction, or both compared to approximately 50% treatment retention in some trauma-focused psychotherapy clinical trials .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tends to occur when C&A providers achieve better outcomes at lower costs and with fewer pharmacologic side effects—a benefit that cannot be understated given the opioid crisis. For these reasons, Medicare covers acupuncture for lower back pain, and the Veteran's Administration covers acupuncture for use in PTSD (Tang et al 2023). In such cases, C&A may be a viable substitute, which should improve health outcomes and spark competition on these therapies.…”
Section: How New Health Care Providers Disrupt Exchangesmentioning
confidence: 99%